Capitalismo, políticas sociais e criminalização dos pobres - Souza, Izaque Pereira de (2012)
This paper presents the results of violence analysis elements and the criminalization of poor, as well as some of its developments in the field of social and educational policies in the context of capitalism - the latter included as part of the first. Therefore, we review the main changes in the capitalist mode of production and how these changes affected the relationship between the State, ways of production and society. We demonstrate that as far as the dictates of Big Capital and the State shall proceed to incorporate such ideologies, concepts of democracy and equality become relativized. Also, the role of the state - which should be to mediate relations with a view to ensure equal treatment to all - is not the case of practicing. Thus, overestimating the precepts of the mode of production and ignoring the individual needs is to have an environment in which there is a decrease in the welfare state and, in order to contain the emergence of conflicts, the growth of a criminal state, violent, repressive, and especially suited for the layers seen as subordinated. From these conflicts, generated by the process of capital accumulation and bitter absence from the state - that is remiss not to interfere with this process, is beginning a new meaning with a regard to violence and crime: it creates the need for identify the "enemies" who must be controlled; speeches are now turning to quick fixes and not structural. In the field of social policies, measures are being fueled immediacy of nature and merely welfare, the policies in the field of criminal / penal has been getting hard, this hardening, which follows a request from society and goes to live in a climate of insecurity and fear, policies toward education in this context become redemptive treated - as if they had conditions per se equate social ills and avoid directing the individual to crime. And as we were delving in our analysis we noticed that all the proposed capital movements legitimized by the state in order to guarantee "social peace and order" would indeed keep the hegemonic character of capitalism and the legitimacy of a bourgeois society.